2011
DOI: 10.1590/s0103-84782011005000017
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades químicas de um Argissolo tratado sucessivamente com composto de lixo urbano

Abstract: In order to assess the changes in some chemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
12

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
1
10
0
12
Order By: Relevance
“…Almeida et al (2008) showed that applications of alkaline wastes from the pulp and paper industry promoted an improvement in soil fertility, especially in relation to acidity correction. Krob et al (2011), worked with the application of urban wastes to soil and observed increasing pH, organic matter P, C, Ca…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al (2008) showed that applications of alkaline wastes from the pulp and paper industry promoted an improvement in soil fertility, especially in relation to acidity correction. Krob et al (2011), worked with the application of urban wastes to soil and observed increasing pH, organic matter P, C, Ca…”
Section: Introductionmentioning
confidence: 99%
“…The use of urban waste compost in agriculture allows the cycling of organic matter and nutrients (Melo et al, 2011), and thus helps to maintain or restore soil chemical, physical and biological properties (Kray et al, 2011;Krob et al, 2011). In this sense, several studies have addressed the changes in soil chemical properties and plant nutrition induced by the application of urban waste compost (Sampaio et al, 2010;Krob et al, 2011;Lima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several studies have addressed the changes in soil chemical properties and plant nutrition induced by the application of urban waste compost (Sampaio et al, 2010;Krob et al, 2011;Lima et al, 2011). Strojaki et al (2013) found that successive applications of urban waste compost to an Oxisol in the northwestern region of Rio Grande do Sul led to a decrease in potential acidity and increases in soil cation exchange capacity, base saturation, and exchangeable calcium and magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the values of OM and V of the soil with the addition of organic fertilizers are reported in the literature (Strojaki et al, 2013). The increment of OM promotes improvements of soil chemical and physical attributes, resulting in greater availability of nutrients, permeability and water movement in the soil (Krob et al, 2011;Sampaio et al, 2012), besides providing organic acids that are important for the solubility of the minerals and increment in the recycling and mobility of nutrients (Pavinato & Rosolem, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…The organic matter supplied through organic fertilizers improves soil chemical and physical characteristics and reduces costs with chemical fertilizers, besides allowing better use and storage of water in the soil (Krob et al, 2011;Sampaio et al, 2012).…”
Section: Introductionmentioning
confidence: 99%